2018
DOI: 10.1101/328385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theoretical Tool Bridging Cell Polarities with Development of Robust Morphologies

Abstract: Despite continual renewal and damages, a multicellular organism is able to maintain its complex morphology. How is this stability compatible with the complexity and diversity of living forms? Looking for answers at protein level may be limiting as diverging protein sequences can result in similar morphologies. Inspired by the progressive role of apicalbasal and planar cell polarity in development, we propose that stability, complexity, and diversity are emergent properties in populations of proliferating polar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 95 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…A natural extension of this work would be to include planar cell polarity, which can induce tubulogenesis and thus branching 26 , and cell differentiation, which could contribute to self-organization of cells within organoids through differential adhesion as well as to programmed shape formation through spatial modulation of apico-basal polarity. To better describe the typical experimental setup in growing organoids, the model could consider tissue growth on curved substrates and include viscous dissipation at the tissue-matrix interface, which may promote buckling and branching 27 .…”
Section: Discussionmentioning
confidence: 99%
“…A natural extension of this work would be to include planar cell polarity, which can induce tubulogenesis and thus branching 26 , and cell differentiation, which could contribute to self-organization of cells within organoids through differential adhesion as well as to programmed shape formation through spatial modulation of apico-basal polarity. To better describe the typical experimental setup in growing organoids, the model could consider tissue growth on curved substrates and include viscous dissipation at the tissue-matrix interface, which may promote buckling and branching 27 .…”
Section: Discussionmentioning
confidence: 99%
“…One exception is an article by Hogeweg (Hogeweg, 2000) using a 2D Potts model with a boolean gene network, extracellular signaling and cell adhesion to show that morphogenesis can evolve as a side effect of natural selection for diversity of cell types. The other exception is the work of Nissen et al (Nissen et al, 2018). This work uses a 3D model including cell division, cell polarization and adhesion in epithelial cells without cell-cell extracellular signaling or gene networks.…”
Section: Discussionmentioning
confidence: 99%
“…This means that there is no clear way to connect the model parameters to in vivo ones in three-dimensional systems. On the other hand, particle-based cellular models can also assume parameters other than the potential of cell-cell interactions, leading to recapitulation of complex three-dimensional structures such as the blastocyst [84][85][86] . In particular, a recent study reported a model that considered cell polarities, in which transformation from cell aggregates to cell sheets and bending of cell sheets were simulated 86 .…”
Section: Usefulness Application and Limitation Of Inference Methodsmentioning
confidence: 99%
“…On the other hand, particle-based cellular models can also assume parameters other than the potential of cell-cell interactions, leading to recapitulation of complex three-dimensional structures such as the blastocyst [84][85][86] . In particular, a recent study reported a model that considered cell polarities, in which transformation from cell aggregates to cell sheets and bending of cell sheets were simulated 86 . Particle-based models have also been expanded by considering cell shapes, where a cell is composed of two particles or a Voronoi tessellation is combined to implement multibody effect 22,28,31,57,63,87,88 , and mechanical properties and dynamics of self-propelled cells or cell aggregates were investigated.…”
Section: Usefulness Application and Limitation Of Inference Methodsmentioning
confidence: 99%
See 1 more Smart Citation